2021
DOI: 10.3346/jkms.2021.36.e315
|View full text |Cite
|
Sign up to set email alerts
|

Growth in Exclusively Breastfed and Non-exclusively Breastfed Children: Comparisons with WHO Child Growth Standards and Korean National Growth Charts

Abstract: Background This study examined the relationship of infant feeding with anthropometric indices of children during their first six years of life relative to the Korean National Growth Charts (KNGC) and the World Health Organization Child Growth Standards (WHO-CGS). Methods The study population consisted of 547,669 Korean infants and children who were 6 months-old to 6 years-old (born in 2008–2009) and participated in the National Health Screening Program for Infants and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
3
2
0
Order By: Relevance
“… 20 21 22 23 24 A recent Korean study showed that children who were exclusively breastfed for the first 6 months of life were shorter and lighter up to approximately 4 years of age than mixed- or formula-fed children. 25 Our results are similar, possibly because more than 2/3 of children with PBF were fully breastfed for 6 months. In addition, the number of children with WAZ < −1 (mildly underweight) 26 27 was significantly greater among children with PBF, although only two of them had WAZ < −2.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“… 20 21 22 23 24 A recent Korean study showed that children who were exclusively breastfed for the first 6 months of life were shorter and lighter up to approximately 4 years of age than mixed- or formula-fed children. 25 Our results are similar, possibly because more than 2/3 of children with PBF were fully breastfed for 6 months. In addition, the number of children with WAZ < −1 (mildly underweight) 26 27 was significantly greater among children with PBF, although only two of them had WAZ < −2.…”
Section: Discussionsupporting
confidence: 73%
“…In a Korean pediatric study comparing body mass index (BMI) up to 6 years of age according to the infant feeding method, there was no significant difference in BMI between the children with 6 months EBF and those without, except for the 2-years-old age group. 25 Therefore, further research on this subject with school-age Korean children is needed to determine the clinical significance of the relatively low protein intake in toddlers with PBF compared to those without PBF in our study population.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research on how and by when breastfed children's growth differs from formula-fed children depends on the conditions of the study population and growth measurement parameters. 22 23 24 25 26 A recent Korean study of infants and toddlers from the NHSPIC found that infants who were exclusively breastfed for six months before the age of four were shorter and weighed lesser than those who were not, consistent with our findings. 23 However, the degree of significance of the growth difference during 24–35 months of age was less than that during 12–23 months of age using the same methodology, 15 with the difference in weight averaging 200 g vs. 400 g and the difference in weight gain decreasing from a 0.2 to 0.13.…”
Section: Discussionsupporting
confidence: 91%
“… 22 23 24 25 26 A recent Korean study of infants and toddlers from the NHSPIC found that infants who were exclusively breastfed for six months before the age of four were shorter and weighed lesser than those who were not, consistent with our findings. 23 However, the degree of significance of the growth difference during 24–35 months of age was less than that during 12–23 months of age using the same methodology, 15 with the difference in weight averaging 200 g vs. 400 g and the difference in weight gain decreasing from a 0.2 to 0.13. Additionally, the difference in height was not significant at age 2 years, nor was the difference in obesity.…”
Section: Discussionsupporting
confidence: 91%
“…Possible explanations for our study results’ statistical insignificance include the small sample size, resulting in a decrease in the statistical power. Additionally, the effect of PAH exposure on the adiposity in children aged 3–5 years might be less significant compared to other environmental factors such as nutritional and socioeconomic statuses [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%